O uso dos Objetivos do Desenvolvimento Sustentável [ODS] e do indicador de sustentabilidade Programa Cidades Sustentáveis [PCS] para uma urbanização sustentável e social na cidade de Barueri - SP - Mizutani, Meriellen Nuvolari Pereira (2019)
The recurrent dynamic in the growth of cities causes damage to the environment, and the cities themselves suffer consequences of this acc exelerated and disorganized human occupation, being necessary to change the ways of thinking the planning and management of urban spaces. Given this, it is essential to address the reflection and practice regarding sustainability issues within the planning and organization of cities, because their infrastructure and other social investments need to be understood as perennial benefits, to be enjoyed also in the future. Associated with the new sustainable agendas that the country has been committing to, the use of indicators as a tool for a more orderly and sustainable growth, seeking to reduce inequities within large, medium and small cities, helps the political, strategic and business decisions of managers. aiming to attend beyond the objectives of economic and environmental order, similarly to social, cultural, physical and political issues, enabling a better quality of life of the citizen and a more equitable use of spaces. In this sense, the present research sought to study the principles and concepts regarding sustainable urban development, the use of sustainability indicators as a tool to the processes for urban planning, specifically the Sustainable Cities Program [PCS] in its axis 5, in council. with the goals of the Sustainable Development Goals [SDG] focused on goal 11 Sustainable cities and communities. The PCS is a very encouraged indicator within Brazilian cities since 2012, especially in the city of Barueri - SP - Brazil, defined as the area of study of this research. It was adopted as a clipping criterion for the analysis inloco two neighborhoods, one with larger and the other with lower Municipal Human Development Index [MHDI]. The research is classified as exploratory qualitative, and was based on bibliographic survey and documentary records, semi-structured interviews forming the quadruple helix (government, organized civil society, companies and universities), participant and direct observation. The results presented allowed reflections on the results obtained with the use of indicators within the municipal urban planning, pointing out that the achievement of urban sustainability and the reduction of socio-spatial inequalities is difficult and not reaching within the city of Barueri, but it is possible to reach, depending on the link between public, private and collective involvement.